EFFECT OF AEROBIC AND ANAEROBIC TRAINING ON DIFFERENT ERGOMETERS IN RAT MUSCLE AND HEART TISSUES - Ozaki, Guilherme Akio Tamura; Filho, José Carlos Silva Camargo [UNESP]; Garcia, Thiago Alves; Castoldi, Robson Chacon; Belangero, William Dias (FapUNIFESP (SciELO), 2022)
Objective: Analyze the effects of aerobic and anaerobic training on different ergometers on muscle and cardiac hypertrophy in rats. Methods: The animals were separated into the following groups: Control (C), Aerobic Training in Water (ATW), Resistance Training in Water (RTW), Aerobic Training on Treadmill (ATT), and Resistance Training in Climbing (RTC). All training protocols were carried out for 4 weeks, 3 times/week. The cross-sectional area (CSA) of the gastrocnemius muscle cells and the areas of the cardiomyocytes were measured. Results: In the fast-twitch fibers, there was an increase in CSA in the RTW and RTC groups compared to the ATW (p<0.01 and p<0.01) and ATT groups (p<0.01 and p<0.01). In the slow-twitch fibers, the ATW and ATT groups demonstrated a lower CSA compared to the RTW (p=0.03 and p<0.00) and RTC groups (p<0.01 and p<0.01). In the cardiomyocytes, there was an increase in the area of the RTW and RTC groups compared to groups C (p<0.01; p<0.01), ATW (p=0.02; p<0.01), and ATT (p<0.01; p<0.01). Conclusion: The anaerobic training effectively promotes hypertrophy in the fast-twitch fibers and the cardiomyocytes. Level of Evidence V; Animal experimental study
EFEITO DOS TREINAMENTOS AERÓBIO E ANAERÓBIO EM DIFERENTES ERGÔMETROS NOS TECIDOS MUSCULAR E CARDÍACO DE RATOS
Keywords: Cardiac; Muscle fibers; Myocytes; Physical endurance; Resistance training; Skeletal